A temática sexualidade como geradora de uma proposta interdisciplinar: contribuições para a formação de professores da rede pública - Perdomo Junior, Joelio Dias (2015)
This research was developed with a group of eight high school teachers from public schools in the city of Santa Maria/RS, over the years 2013 and 2014, and presents the relationships that can be established between continuing teacher education, sexuality and interdisciplinarity. This study is characterized as qualitative and quantitative and was divided into two manuscripts. The first aimed to investigate the perceptions of teachers about interdisciplinarity. Data collection was made through the application of a questionnaire with opened and closed questions. We found that, for 75% of teachers, the concept/ understanding about interdisciplinarity is the act of integrating curriculum disciplines. We also found that the percentage regarding the teachers who report ever have tried or/developed interdisciplinary activities was around 88%. In the teachers view, the categories that hinder/limit the development of interdisciplinary actions are lack of time, workload, formation and planning. We conclude that most teachers have a superficial knowledge about interdisciplinarity and thus we realized the need to develop actions to minimize this reality, such as continuing teacher education courses. The second manuscript aimed to investigate the construction of an interdisciplinary proposal by teachers for the first grade (1st year) high school, based on the theme sexuality. We decided to analyse the completed proposal and we can see that the teachers discussed issues related to sexuality, not only with respect to the biological aspects, but also and above all the other aspects that surround the lives of individuals, including the social, cultural , economic and political. Teachers also pointed methodological strategies to develop the proposal for the students, such as discussions, textual production and reflexive actions. We conclude, focusing on use of the interdisciplinary approach built by teachers, that it is an alternative resource for the teaching of sexuality.